2021
DOI: 10.1128/msystems.00951-21
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Specificity of Chemoreceptor Profiles in Plant-Associated Bacteria

Abstract: Considering the enormous variety of LBDs at sensor proteins, an important question resides in establishing the forces that have driven their evolution and selection. We present here the first clear demonstration that environmental factors play an important role in the selection and evolution of LBDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 65 publications
0
35
0
Order By: Relevance
“…For example, Helicobacter pylori infects the gastric epithelium and is adapted to a highly specific niche. This species has 4 chemoreceptors, which is a number significantly below the bacterial average of 14 ( 1 ). Analysis of H. pylori chemoreceptor function has revealed a specialized spectrum of chemoeffectors that is closely linked to establishing an infection in the stomach.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, Helicobacter pylori infects the gastric epithelium and is adapted to a highly specific niche. This species has 4 chemoreceptors, which is a number significantly below the bacterial average of 14 ( 1 ). Analysis of H. pylori chemoreceptor function has revealed a specialized spectrum of chemoeffectors that is closely linked to establishing an infection in the stomach.…”
Section: Introductionmentioning
confidence: 95%
“…Chemotaxis allows bacteria to move in chemical concentration gradients and facilitates the colonization of more-favorable ecological niches. Genome analyses indicate that about half of known bacterial species possess genes required for chemotaxis ( 1 ). The molecular machinery for chemotaxis is highly complex and is among the best-studied bacterial signal transduction systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In phytopathogenic bacteria, the importance of chemotaxis for efficient plant infection is supported by abundant experimental evidence (Antúnez‐Lamas, Cabrera‐Ordonez, et al, 2009; Antúnez‐Lamas, Cabrera, et al, 2009; Cerna‐Vargas et al, 2019; Hawes & Smith, 1989; Hida et al, 2015; Kumar Verma et al, 2018; Malamud et al, 2011; Matas et al, 2012; Santamaría‐Hernando et al, 2020; Tumewu et al, 2020; Yao & Allen, 2006, 2007). The relevance of chemotaxis is also reflected by the fact that about 90% of phytopathogenic bacteria possess chemosensory genes (Ortega, Zhulin, et al, 2017), whereas such genes are only found in 47% of total bacteria (Sanchis‐López et al, 2021). In addition, phytopathogenic bacteria harbour on average 27 chemoreceptor genes (Lacal et al, 2010), a number that is well above the bacterial average of 13 (Sanchis‐López et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of chemotaxis is also reflected by the fact that about 90% of phytopathogenic bacteria possess chemosensory genes (Ortega, Zhulin, et al, 2017), whereas such genes are only found in 47% of total bacteria (Sanchis‐López et al, 2021). In addition, phytopathogenic bacteria harbour on average 27 chemoreceptor genes (Lacal et al, 2010), a number that is well above the bacterial average of 13 (Sanchis‐López et al, 2021).…”
Section: Introductionmentioning
confidence: 99%